Measures of environmental and sustainable socioeconomic welfare and the political economy of capitalism - theoretical reconstruction, technical specification, and critical analysis: GDP, ISEW and GPI - Brennan, Andrew John (Curtin University, 2009)
This study undertakes a critical analysis of measures of environmental and sustainable socioeconomic welfare from the perspective of political economy. One of the prime motivations for such an inquiry is that Gross Domestic Product (GDP) provides an inadequate measure of social and ecological waste in the economic system. Good measures with solid theory (or theories) can offer vital insights where there may be conflict between the various spheres of economy, society and ecology. The inquiry centres on measures that may be referred to as 'Net Income Indices' or Sustainable Economic Welfare Indicators (SEWls), since they are designed for assessing aspects of sustainability and welfare. Commencing in 1972 and ending in April 2009, there have been forty-five individual studies involving construction of a SEWI. SEWls are worthy of a comprehensive appraisal as it is generally accepted that the indices are necessary, workable and adequate measures. This study embarks on a systematic, detailed and scholarly examination of the conclusions drawn in the relevant literature on SEWls, focusing on the calibre of their theoretical, empirical and technical foundations, historical specificity vis-a-vis business cycles and institutional dynamics.For any study into sustainable well-being, the key focus is the effects of market institutions on society. GDP has many limitations, but GDP is charged with significance because it aids our understanding of the capitalist system, however, the same cannot be said for SEWls. It is argued that the net income indices are not very good measures of environmental and social welfare: many authors provide no major good or detailed advancement in theory and no one provides a strong socio-historical institutional analysis. Critically absent from every SEWI analysis is a systematic understanding of the political economy and system dynamics of capitalism. This led to the major hypothesis, which states: understanding the political economy of capitalism will provide vital insights into SEWIs. SEWI advocates have started with ceteris paribus assumptions where medium and long-term processes are not affecting the socioeconomic system. Because ad-hoc commonsensical accountancy prevails, the authors are inadequately accounting for the present well-being effects on the social structure, and do not consistently, as done for ecological capital depreciation, value the future generational costs (lost services) of an (un)sustainable social capital and human-health capital base. SEWI restricts the analysis to a few monetary variables and thereby it is too inflexible and not very helpful.Yet, such social services and disservices are elementary for critically evaluating the multiple contradictions of capitalism in a disembedded economy (where the 'economy' tends to dominate other aspects of culture). Multiple contradictions assess the complexity of the disembedded economy better than single contradictions. SEWI advocates focus mainly on the contradiction (i.e. the trade-off) between the natural environment and consumption goods, and their inquiry is, at the most, limited to the national level. It is argued that they are in a one-and-a-half contradiction world: they see primarily one contradiction and a partial social reality from a very nationalistic perspective. In the global disembedded economy, all areas of life are both relatively autonomous yet interconnected. There are multiple contradictions of capitalism to be explored, but it is hard to link all of them in one index. It is necessary to transcend the one-and-a-half contradiction world and have a broad view of wealth.It is difficult to determine the true nature of the "service" and its distribution to persons-in-community in an exclusive aggregated net-income index. Composite net-income indicators inadequately measure distribution. Without fundamentally understanding the heterogeneous power relations that define the system's reproduction, applications of 'Net Income Indices' are ineffective. It is argued that there are major limits to which SEWls can be transformed or radically redeveloped within the context of the political economy critique. The crux of the problem is that SEWI advocates fail to incorporate an understanding of the historical socioeconomic system of capitalism (as the fundamental background condition), which affects their whole project. A tendency for the literature to abstract from real trends in the disembedded economy is apparent because of the weak institutional apparatus, mechanical applications, and conceptual difficulties. This thesis raises questions about the competence of SEWls to deal with real-world problems. A more detailed and broader approach to sustainable well-being is needed to find the root of social and environmental problems.